Lanthanum nanocluster/ZIF-8 for boosting catalytic CO2/glycerol conversion using MgCO3 as a dehydrating agent. Issue 11 (22nd February 2021) - Hu, Chechia; Chang, Chien-Wei; Yoshida, Masaaki; Wang, Ke-Hsuan
Abstract : La/ZIF-8 was effective in converting CO2 /glycerol to glycerol carbonate. La 3+ –O 2− pairs of La2 O3 on ZIF-8 could strengthen the Lewis basicity and acidity. MgCO3 could physically adsorb water molecules as a dehydrating agent. Abstract : A lanthanum-modified zeolitic imidazolate framework (La/ZIF-8) was developed to produce glycerol carbonate using CO2 and glycerol as raw materials. La/ZIF-8 provides a high catalytic glycerol conversion efficiency owing to its surface-attached nanoclusters of La2 O3, which can be viewed as La 3+ –O 2− pairs that strengthen the Lewis basicity and acidity, and the large specific surface area of ZIF-8. The catalytic glycerol conversion and the yield of glycerol carbonate were 46.5% and 35.3%, respectively, using CH3 CN as a dehydrating agent. With increase in the amount of CH3 CN, the water molecules could react with CH3 CN to reduce the selectivity. When an inorganic dehydrating agent, MgCO3, was used to physically adsorb and remove water molecules in the reaction, the selectivity of the reaction could be increased to over 95%, which is the highest ever reported. Reaction kinetics analysis also revealed that the activation energy of using MgCO3 (5.4 kJ mol −1 ) as a dehydrating agent is lower than that using CH3 CN (7.8 kJ mol −1 ). Moreover, the La/ZIF-8 could be recycled and reused at least three times with high catalytic performance. This study provides an effective material with dual Lewis basicity and acidity for CO2 /glycerol conversion and significantly improves the catalytic performance using an inorganic dehydrating agent.